PERLINDUNGAN KONSUMEN TERKAIT IKLAN MOBIL MELALUI MEDIA TELEVISI - Tangkas Hadi Perwira, (2021)
This study aims to identify and explain the causes of the criminal act of spreading fake news (hoaxes) on social media. And to find out and explain about law enforcement efforts against perpetrators of criminal acts of spreading fake news (hoax) in Indonesia so as not to disturb the public and disturb public peace and order. The theory used is the theory of law enforcement, the theory of responsibility, and the theory of criminal acts. The research method used is a normative legal research method with a qualitative approach. The results of this study formulated that it is easy for people to have modern and inexpensive communication tools, in this case the use of smartphones as a medium for information retrieval. The public is easily influenced by unclear issues without verifying or confirming the truth of the information / news, so they immediately take action to share information that is not yet clear. Lack of interest in reading, so there is a tendency to discuss news not based on accurate data, only relying on memory or unclear sources. In addition, other supporting factors are political and educational factors. For law enforcement, RatnaSarumpaet as the perpetrator of the spread of fake news (hoax) has been charged based on the criminal threat in the provisions of Article 14 paragraph (1) of Law Number 1 Year 1946 regarding Criminal Law Regulations, and Article 28 paragraph (2) Jo Article 45 A paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. The conclusion is that the factors causing the spread of fake news (hoaxes) on social media are due to the high number of social media users that are not proportional to the level of literacy education that can be accepted by social media users in distinguishing between fact-based news and hoaxes. ) and is supported by sharing features that make it easier for the social media community (netizens) to receive hoaxes disseminated by hoax actors / creators on social media, such as Whatsapp, Tweeter, and Facebook which have the most dominant influence on the media community social (netizens) to make fake news go viral. Law enforcement efforts against perpetrators of criminal acts of spreading fake news (hoax) in Indonesia are carried out by enforcing criminal law by implementing imprisonment as an effort to provide a deterrent effect and a warning to the Indonesian people that the act of spreading fake news (hoax) is a criminal act that can be threatened with criminal sanctions in accordance with the provisions of positive law in force in Indonesia.